Family Commitments and Career Success: Earnings of Male and Female Managers - Cannings, Kathy (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1991)
The dual-career family, with its attendant pressures for dual commitment to the home and to the career, has become an increasingly important phenomenon in recent decades. This paper uses a firm-level data set to examine the impact of family commitments as well as cognitive, behavioral, and organizational factors on the earnings of 519 married middle managers in a large Canadian corporation. Alongside a number of behavioral variables as well as the functional division of managerial labor in the company, division of labor in the employee's household has a significant impact on managerial earnings. The inclusion of a variable reflecting the household division of labor in the managerial earnings function helps to explain a substantial proportion of the earnings disadvantage of women in this company that might otherwise simply be attributed to gender.